Longitudinal Rise in Seroprevalence of SARS-CoV-2 Infections in Children in Western Germany-A Blind Spot in Epidemiology? - Folke Brinkmann; Hans H. Diebner; Chantal Matenar; Anne Schlegtendal; Jan Spiecker; Lynn Eitner; Nina Timmesfeld; Christoph Maier; Thomas Lücke (MDPI AG, 2021)
SARS-CoV-2 infection rates in children and adolescents are often underestimated due to asymptomatic or oligosymptomatic infections. Seroprevalence studies can reveal the magnitude of "silent" infections in this age group and help to assess the risk of infection for children but also their role in spreading the disease. In total, 2045 children and their parents from the Ruhr region were finally included after the exclusion of drop-outs. Seroconversion rates among children of all age groups increased from 0.5% to 8% during the study period and were about three to fourfold higher than the officially registered PCR-based infection rates. Only 41% recalled symptoms of infection; 59% were asymptomatic. In 51% of the infected children, at least one parent also developed SARS-CoV-2 antibodies. Depending on local incidences, the rates of seroconversion rose to different levels during the study period. Although the dynamics of infection within the study cohort mirrors local incidence, the figure of SARS-CoV-2 infections in children and adolescents appears to be high. Reported contact with SARS-CoV-2-infected individuals in the same household carries a high risk of infection.